A genome-wide association study identifies genetic variants associated with hip pain in the UK Biobank cohort (N = 221,127) - Qi Pan; Yiwen Tao; Tengda Cai; Abi Veluchamy; Harry L. Hebert; Peixi Zhu; Mainul Haque; Tania Dottorini; Lesley A. Colvin; Blair H. Smith; Weihua Meng (Scientific Reports)
Abstract Hip pain is a common musculoskeletal complaint that leads many people to seek medical attention. We conducted a primary genome-wide association study (GWAS) on the hip pain phenotype within the UK Biobank cohort. Sex-stratified GWAS analysis approach was also performed to explore sex specific variants associated with hip pain. We found seven different loci associated with hip pain at GWAS significance level, with the most significant single nucleotide polymorphism (SNP) being rs77641763 within the EXD3 (p value = 2.20 × 10–13). We utilized summary statistics from the FinnGen cohort and a previous GWAS meta-analysis on hip osteoarthritis as replication cohorts. Four loci (rs509345, rs73581564, rs9597759, rs2018384) were replicated with a p value less than 0.05. Sex-stratified GWAS analyses revealed a unique locus within the CUL1 gene (rs4726995, p = 2.56 × 10–9) in males, and three unique loci in females: rs1651359966 on chromosome 7 (p = 1.15 × 10–8), rs552965738 on chromosome 9 (p = 2.72 × 10–8), and rs1978969 on chromosome 13 (p = 2.87 × 10–9). This study has identified seven genetic loci associated with hip pain. Sex-stratified analysis also revealed sex specific variants associated with hip pain in males and females. This study has provided a foundation for advancing research of hip pain and hip osteoarthritis.